Clinical application and research progress of auricular acupoint therapy in prevention and treatment of common gynecological diseases (耳穴疗法在妇科常见病防治中的临床应用及研究进展) - REN Xiuya (任秀亚); XIE Wei (谢薇); HE Yanlin (何燕琳); CHEN Ying (陈英); XIANG Yiming (向毅明); ZHAO Lingling (赵玲玲); ZHOU Yihan (周艺涵); LUO Liyuan (罗丽媛) (中西医结合护理)
Auricular acupoint therapy, as an appropriate technique of Traditional Chinese Medicine nursing operation, has a certain curative effect in preventing and treating common gynecological diseases. The paper reviewed the auricular acupoint therapy in prevention and treatment of common gynecological diseases from six aspects of menstrual disorders, chronic pelvic inflammatory disease, primary dysmenorrhea, perimenopausal syndrome, acute mastitis, and breast hyperplasia, in order to provide a certain reference for the treatment of gynecological diseases by external therapy of traditional Chinese medicine. (耳穴疗法作为一种中医特色护理操作适宜技术, 在防治妇科常见疾病方面具有一定疗效。本文分别从月经不调、慢性盆腔炎、原发性痛经、围绝经期综合征、急性乳腺炎、乳腺增生六个方面进行综述, 以期为中医外治法治疗妇科疾病提供一定的参考。)